Shackled feet: A review of women entrepreneurs' challenges in developing countries - Md. Mizanur Rahman; Salamzadeh Aidin; Leo Paul Dana (Entrepreneurial Business and Economics Review (EBER), 2024)
Objective: The fundamental objective of this systematic literature review (SLR) is to explore the current challenges for women entrepreneurs in developing countries and discuss future research opportunities. Research Design & Methods: We applied a SLR approach to fulfil the objective. We selected 29 articles from SCOPUS and Google Scholar databases to synthesize reviews. To ensure the quality of the articles collected from Google Scholar, we used Scimago Journal & Country Rank (SJR). Findings: We categorised the key findings into themes (T), contexts (C), and methodologies (M). The major challenges for women entrepreneurs in developing countries cover five themes, i.e. (1) financial, (2) socio-cultural, (3) educational and skills, (4) networking and marketing, (5) political and legal. Developing countries were the main context (C) of this review. Regarding methodologies (M), 51.72% of the collected articles were qualitative. Implications & Recommendations: Policymakers can help make more specialized women entrepreneurship policies by assembling research identifying national barriers empirically and drawing comparisons between the realities of both countries and regions. We proposed a conceptual framework or model based on the challenges of women entrepreneurship and other future research agendas. Contribution & Value Added: This review article is one of the leading studies which helps academics, researchers, and readers gain a deeper understanding of challenges for women entrepreneurs in developing countries by providing a foundation for future studies and encouraging researchers to investigate this topic.
Keywords: L26; 330; challenges; developing countries; economic development; entrepreneurship; systematic literature review; women